Serological Relationships of Cryptococcus spp.: Distribution of Antigenic Factors in Cryptococcus and Intraspecies Diversity - Ikeda, Reiko (American Society for Microbiology, 2000)
The antigenic formulas of 34 species in the genus Cryptococcus were determined by using type strains and eight factor sera prepared from adsorption experiments with Cryptococcus neoformans serotypes. These antigenic factors were shared by 19 species. The strains used could be divided into eight serological groups. The patterns of groups 1, 2, 3, 5, and 6 were the same as the patterns of C. neoformans serotypes A, D, A-D, B, and C, respectively. The species belonging to group 4 reacted to factor sera 1, 2, and 3. Group 7 contained one species that reacted only to factor serum 1. The 15 species in group 8 did not react to any of the factor sera used. Compared to the reported molecular phylogenetic tree, the serological and phylogenetic data were correlated in the Filobasidium lineage. All the members of the albidus clade in the Filobasidium lineage had antigens 1, 2, and 3, and all the strains in the magnus clade belonged to serogroup 8. Moreover, intraspecies diversity was examined using strains of C. curvatus, C. humicolus, and C. laurentii. Serological heterogeneity was observed in the species C. humicolus and C. laurentii, as well as in phylogenetic relationships previously published. Using serological features, similarities and differences between Cryptococcus species were demonstrated. Our study contributes to a better description of the genus Cryptococcus and related species phenotypically and phylogenetically.